Genetic basis of hypertrophic cardiomyopathy in children - Rupp, Stefan; Felimban, Moataz; Schänzer, Anne; Schranz, Dietmar; Marschall, Christoph; Zenker, Martin; Logeswaran, Thushiha; Neuhäuser, Christoph; Thul, Josef; Jux, Christian; Hahn, Andreas (Clinical research in cardiology, 2019)
Background Previous investigations assessing the genetic cause of pediatric hypertrophic cardiomyopathy (HCM) found underlying genetic mutations in 50–60% of cases. The purpose of our study was to analyze whether this number can be augmented by applying next-generation sequencing and directing further diagnostics by discussing unsolved cases in a multidisciplinary board. Methods and results 42 patients with the diagnoses of HCM made before age 18 years were treated in our center from 2000 to 2016. Genetic analysis was performed in 36 subjects, a genetic defect was detected in 29 (78%) patients. 15 individuals (42%) had pathogenic variants in genes encoding sarcomere proteins, and 5 (14%) in genes coding for components of the RAS/MAPK signaling pathway. 4 subjects (11%) had mutations in the GAA gene (Pompe disease), and 3 (8%) had Frataxin repeat expansions (Friedreich’s ataxia). One patient each showed a mutation in BAG3 and LMNA. Discussion of unsolved HCM cases after performing next-generation sequencing (28 genes) in an interdisciplinary board unraveled the genetic cause in 9 subjects (25%). Conclusion A definite genetic diagnosis can be reached in nearly 80% with HCM of childhood onset. Next-generation sequencing in conjunction with a multidisciplinary cooperation can enhance the diagnostic yield substantially. This may be important for risk stratification, treatment planning and genetic counseling.